ANALISIS PERSEPSI KONSUMEN PADA PRODUK AIR MINERAL DALAM KEMASAN (AMDK) MEREK AZHOM - Eva Fauziana; Lili Fadli Muhammad (SMART Management Journal, 2022)
The purpose of this study is to analyze the consumer perception of the mineral water brand Azhom. The research methodology used a qualitative approach by having face-to-face interviews with around 100 owners of street vendors and kiosks. The research results showed the consumers' analysis of mineral water Azhom and how its management could develop detail strategies to develop products, win the market and do market penetration. The research limitation was the number of respondents and the areas to be surveyed were still limited. The research contributions are to gain teamwork among the Azhom product owner and the kiosk and street vendor owner to increase Azhom sales which also develops better economic values.